"Jeg gråter noen tårer hver dag". En fenomenologisk studie av hjemmeboende kreftpasienters beskrivelse av deres livvsituasjon i palliativ fase - Sønning, Hildegunn Ervik; Fossum, Mariann (Nordisk tidsskrift for helseforskning, 2020)
"I cry a few tears every day". A phenomenological study of at-home cancer patients' description av their life situations under palliativ careThe aim of this study was to investigate how at-home cancer patients perceived their life situations during the palliative care phase. The study employed a qualitative exploratory research design involving in-depth personal interviews with six women and two men between the ages of 35 and 63. All the interviewees lived at home, experiencing different life situations and suffering from different types of cancer. The interviews were recorded and transcribed verbatim. Data analysis was carried out using the descriptive phenomenological method presented by Giorgi. The findings are grouped under four themes; living with uncertainty and future unpredictability, perceptions of being seen and heard in encounters with health professionals and others, stress associated with the perception of disappointing close relatives, and challenges linked to meeting everyday demands. The patients’ stories relate their views on life, suffering and pain relief.